“Para no vivir en perpetua afectación de un sexo mentido”. Normas de género y travestismo en las primeras décadas del siglo XIX chileno - Undurraga Schüler, Verónica; Montoya Muñoz, Sandra Cristina (Jahrbuch für Geschichte Lateinamerikas, 2025)
This article analyzes gender norms and their negotiation in Chilean society at the beginning of the 19th century. Based on a notorious case of homicide that occurred in 1845, it proposes that the transvestism of masculine identity was tolerated and justified when it was transitory and did not discuss the representation of the masculine identity as superior to the feminine. The study of judicial sources, press, books about the case and correspondence, allows to observe how the adoption of the female identity by a man did not necessarily imply the denial of masculinity, focusing public interest on the honor of the individuals involved.